The Strategic Role of Vocational High Schools in Facing Technological Disruption: A Critical Review and Implications - Yusri, Yusri (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
Technological advances in the Industrial Revolution 4.0 era and the shift towards Society 5.0 require Vocational High Schools to produce graduates who are competent, relevant, and able to adapt to the dynamics of the modern workplace. This study aims to critically analyze the strategic role of vocational high schools in preparing human resources with optimal work readiness. Through a systematic review of 15 studies published between 2021 and 2025, this study identified four main themes: student work readiness, graduate competency relevance, curriculum challenges, and digital competency. The synthesis results indicate that graduate work readiness is shaped by the integration of technical competencies, employability skills, digital literacy, critical thinking skills, industrial practice experience, and psychological aspects such as career adaptability, with soft skills being the most dominant factor. This study also identified several obstacles that reduce graduate relevance, including mismatching competencies with industry needs, a less adaptive curriculum, low teacher digital readiness, and unsustainable industry partnerships. These findings emphasize the importance of curriculum synchronization, strengthening teachers’ pedagogical and digital competencies, optimizing fieldwork practices, and expanding school-industry collaboration. This study has limitations such as the limited number of studies, potential selection bias, and focus on the Indonesian context. Therefore, further research is recommended to test the effectiveness of the IVRM Model using mixed methods, assess the implementation of micro-credentials in various skill programs, and conduct longitudinal studies on the impact of teaching factory implementation and industry partnerships.